IPVPN design in Telekom Malaysian Berhad (TMB) / Rajemah Al Shukriah Ahmad - Ahmad, Rajemah Al Shukriah (2003)
Internet Protocol Virtual Private Network (IPVPN) defines a private network that uses public network infrastructure, Internet to carry data. This research focuses on logical design of an IPVPN that resides on an IP network, which is TMNet for Telekom Malaysia Berhad (TMB). With IP, we provide a cost effective design to the customer instead of using leased line to maintain wide geographical communication. Also, we are applying MPLS architecture which combines the layer 2 switching and Layer 3 routing to improve performance, scalability, reliability and security while IPSec architecture enhance on security to customer's data traffic. This research also concerns about Quality of Service (QOS) that enable to offer differentiated IP based service levels on network traffic.